Nuchal Skinfold Thickness in Pediatric Brain Tumor Patients - Peng, Junxiang; Boekhoff, Svenja; Eveslage, Maria; Bison, Brigitte; Sowithayasakul, Panjarat; Friedrich, Carsten; Müller, Hermann L. (Frontiers in Endocrinology, 2021)
Background: Severe obesity and tumor relapse/progression have impact on long-term prognosis in pediatric brain tumor patients. Methods: In a cross-sectional study, we analyzed nuchal skinfold thickness (NST) on magnetic-resonance imaging (MRI) follow-up monitoring as a parameter for assessment of nuchal adipose tissue in 177 brain tumor patients (40 World Health Organization (WHO) grade 1–2 brain tumor; 31 grade 3–4 brain tumor; 106 craniopharyngioma), and 53 healthy controls. Furthermore, body mass index (BMI), waist-to-height ratio (WHtR), caliper-measured skinfold thickness (cSFT), and blood pressure were analyzed for association with NST. Results: Craniopharyngioma patients showed higher NST, BMI, WHtR, and cSFT when compared to other brain tumors and healthy controls. WHO grade 1–2 brain tumor patients were observed with higher BMI, waist circumference and triceps cSFT when compared to WHO grade 3–4 brain tumor patients. NST correlated with BMI, WHtR, and cSFT. NST, BMI and WHtR were associated with increased blood pressure. In craniopharyngioma patients with hypothalamic involvement/ lesion or gross-total resection, rate and degree of obesity were increased. Conclusions: NST could serve as a novel useful marker for regional nuchal adipose tissue. NST is highly associated with body mass and waist-to-height ratio, and easily measurable in routine MRI monitoring of brain tumor patients.